Retracted: Effect of Sham Acupuncture on Chronic Pain: A Bayesian Network Meta-Analysis. Issue 4 (22nd August 2022) - Zhou, Rui; Zhu, Yan-juan; Chen, Xian; Ma, Hao-chuan; Liu, Yi-hong; Chang, Xue-song; Chen, Ya-dong; Yu, Ya-ya; Xiao, Zhen-zhen; Liu, Li-rong; Li, Yong; Zhang, Hai-bo
Abstract: Background: Along with increasing research on acupuncture for chronic pain, the validity of sham acupuncture (SA) has also been argued. Methods: Nine databases were searched for randomized controlled trials (RCTs) from the inception dates of the databases to July 5, 2022. With Markov Chain Monte Carlo methods, a Bayesian multiple-treatment network meta-analysis (NMA) with random-effects model was conducted. Results: A total of 62 RCTs with 6, 806 patients and four kinds of treatments (real acupuncture [RA], non-acupuncture [NA], penetrative SA [PSA], and non-penetrative SA [NPSA]) were included. The results indicated that both NPSA and PSA were not superior to NA in improving chronic pain (NPSA: mean difference [MD]= –4.77, 95% confidence interval [CI] –11.09 to 1.52; PSA: MD= –4.96, 95% CI –10.38 to 0.48). After NPSA and PSA were combined into the SA group, the weak trend of pain relief from SA was still not statistically significant (MD= –4.91, 95% CI –9.93 to 0.05). NPSA and PSA had similar effects (MD= 0.18, 95% CI –5.45 to 5.81). RA was significantly associated with pain relief, compared with NPSA and PSA (NPSA: MD= –12.03, 95% CI –16.62 to –7.41; PSA: MD= –11.85, 95% CI –15.48 to –8.23). The results were generally consistent regardless of pain phenotype, frequency, duration, acupuncture methods, analgesic intake, or detection bias. Conclusion: These results suggested that acupuncture was significantly associated with reduced chronic pain. The two kinds of placebo acupuncture, NPSA and PSA, have similar effects. Both NPSA and PSA, with a weak but not significant effect, are appropriate to be inert placebo controls in RCTs for chronic pain.